Sustainable Tourism Development: Issues and Strategies for Development in India with Special Reference to the State of Uttaranchal - Mishra, Jitendra Mohan; Gullapalli, Sailaja (Atna Journal of Tourism Studies, 2021)
The state of Uttaranchal is bestowed with immense tourism potential and the following article briefs about Brundtland Commission report and critically examines the sustainable tourism development issues of the state. This article also suggests a sustainable tourism implementation strategy for the state of Uttaranchal. Case studies of Nandadevi National Park, Valley of Flowers, Gomukh/Gangotri Glacier are also presented for a diagnostic discussion.